Intradermal Scalp Closure Using Barbed Suture in Cranial Tumor Surgeries: A Technical Note. Issue 1 (15th July 2018) - Buttrick, Simon S; Eichberg, Daniel; Ali, Sheikh C; Komotar, Ricardo J
Abstract: BACKGROUND AND IMPORTANCE: Traditional scalp closure technique following elective craniotomy involves placement of staples or a continuous running suture. Despite low complication rates, these techniques are often considered to be disfiguring by patients, contribute to the psychosocial trauma of brain surgery, and are associated with discomfort during postoperative staple or suture removal. Some authors have described scalp closure using intradermal absorbable suture, but this technique likely does not reach the tensile strength of closure using traditional methods, and requires knots at the apices of the incision, which can act as a nidus for infection. CLINICAL PRESENTATION: We employed a barbed intradermal closure method in supratentorial elective craniotomies for tumor resection. Complication rates were recorded, and cosmetic outcomes were informally assessed. Intradermal closure with barbed sutures was utilized in 76 patients. At the 2-wk postoperative clinic visit, cosmetic outcomes were excellent in all cases. There was 1 superficial wound infection that presented 6 wk after a pterional craniotomy for low-grade glioma. This resolved with superficial wound revision and oral antibiotic therapy. CONCLUSION: We present a novel scalp closure technique for craniotomies using intradermal barbed Monocryl suture. We have had excellent cosmetic outcomes, and the infection rate of 1.3% compares favorably to published rates. Further studies are required to quantify the improvement in patient satisfaction compared to conventional closure methods.